Applications of systems engineering to distributed-ledger-based cybersecurity management - Lambert, Kent D., author; Bradley, Tom, advisor; Borky, John Michael, committee member; Simske, Steve, committee member; Ray, Indrajit, committee member; Santiago, John, committee member (Colorado State University. Libraries, 2026)
This research identifies a set of practical solutions to the uncontrolled growth of malicious cross-industry cybersecurity threats. Given the presence of the behaviors and negative effects of cyber threats, the research seeks to understand the effects of three eco-system-wide strategies for cyber defense: Defense-in-Depth (DiD), Zero-Trust Architectures (ZTA), and secure cryptographic key provisioning. These strategies are developed using the BlockFrame, Inc., Eco-Secure Provisioning™ (ESP™) Framework, blockchain-assisted digital logistics management and governance, and the application of Emergence Theory and Uniformity. The research addresses five specific questions to organize the approach, with practical translations of this research to selected industrial use cases.
Keywords: digital-privacy; MBSAP; SysML; emergence; cyber-security; MBSE